Domain of the Qur’an from Allameh Tabataba’i’s and Fakhr al-Din Razi’s ViewpointsA Study of Nahj al-Balāgha - ruhollah zeynali; reza keshavarz (پژوهش نامه معارف قرآنی, 2012)
There are three main perspectives regarding the domain of the Qur’an: the maximalist, the minimalist, and the moderate. Fakhr al-Din Razi limits the domain of the Qur’an to religious affairs. For him, these are ideological, moral, and jurisprudence affairs which have been described in full detail in the Qur’an. According to Allameh Tabataba’i, the domain of the Qur’an encompasses maximally all the issues related to the guidance of mankind. In his belief, the Holy Book of Islam covers all issues needed for the guidance.